Dance at Home for People With Parkinson's During COVID-19 and Beyond: Participation, Perceptions, and Prospects - Bek, Judith; Groves, Michelle; Leventhal, David; Poliakoff, Ellen (Frontiers in Neurology, 2021)
Emerging evidence shows that dance can provide both physical and non-physical benefits for people living with Parkinson’s disease (PD). The suspension of in-person dance classes during the COVID-19 pandemic necessitated a transition to remote provision via live and recorded digital media. An online survey explored accessibility of and engagement with home-based dance programs, as well as potential benefits and processes involved in participation. The survey was co-developed by researchers and dance program providers, with input from people with PD and physiotherapists. Responses were collected from 276 individuals, including 178 current users of home-based programs, the majority of whom were participating at least once per week. Among respondents not currently using digital resources, lack of knowledge and motivation were the primary barriers. Most participants (94.9%) reported that home based practice provided some benefits, including physical (e.g., balance, posture) and non-physical (e.g., mood, confidence) improvements. Participants valued the convenience and flexibility of digital participation, but noted limitations including reductions in social interaction, support from instructors and peers, and motivation. There was a strong preference (70.8%) for continuing with home-based practice alongside in-person classes in the future. The results indicate that at-home dance is accessible and usable for people with PD, and that some of the previously-reported benefits of dance may be replicated in this context. Digital dance programs will likely remain a key element of future provision for people with PD, and the present findings will inform further development of resources and research into mechanisms and outcomes of home-based dance participation.